(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Hospitality skills are the skills that are used to provide warm reception and treatment to the guests coming to the hotel. Banquet staff in particular should master these skills as at banquet party/gathering huge number of people gather at one place from various cultures, regions, of various religions and from various backgrounds. Objective: To find out the skills required by Banquet staff; Methodology: Structured questionnaire was prepared on Google Drive and the link was shared on the Facebook and WhatsApp platforms for responses. Results: The ratio of the skilled permanent staff and the contracted unskilled staff was around 3:2 approximately. 88.9% respondents felt satisfied with the services of the hotel, whereas, 11.1% people were unsatisfied with the services of the five star hotel’s banquet services. Conclusion: To overcome the mentioned gap between the expected and delivery, hotels must train their each and every staff in hospitality skills and review them among the staff from time to time. To stand up the expectations of the guests, hotels should hire hotel management graduates and diploma holders in the respective department.